Strategies of combating insurgency in north-eastern Nigeria: a non-traditional approach / Babayo Sule …[et al.] - Sule, Babayo; Yahaya, Muhammad Aminu; Rabiu, Aliyu Alhaji; Ahmad, Muhammad; Hussaini, Kabiru (Universiti Teknologi MARA, 2019)
Insurgency in Northeastern Nigeria has been one of the major national security issues and resulting an international concern for the global agenda of war against terrorism and international security. The insurgency has been consuming thousands of lives and billions of properties in the geo-political region breaching the national security of Nigeria. The problem identified by this paper is the method adopted in fighting against the insurgents especially the traditional security approach has failed to achieve peace, stability, and security in the region for many years since the inception of the insurgency. Thus, the paper has investigated the causes and effects of insurgency in Northeastern Nigeria and also why the current method of addressing the menace of insurgency in the region not yielding the required result. The paper is a conceptual theoretical paper which used qualitative method of data collection and analysis. The data were obtained from primary and secondary sources. Content analysis was used for data analysis and interpretation. The paper has discovered that insurgency in Northeastern Nigeria was caused by long standing socio-economic and political issues such as poverty, ideology, unemployment, ignorance, social exclusion, inequality, and external factors. Thus, for insurgency of this nature to be addressed, need for exploration and utilization of non-traditional or non-military approach such as negotiation, ideological perception, social justice, and equitable distribution of national wealth among all classes in the country are needed.